Professional Competency of PPKN Students in Research Steps on Teaching Seminar Problems - Andrian Andrian (Budapest International Research and Critics University, 2022)
Research or research is an activity to investigate to find by answering a problem formulation through the scientific method systematically. The purpose of this study is to describe how students' professional competence in research steps and critical studies in teaching seminars on educational problems in schools, research methods used to use descriptive qualitative, data collection techniques using interviews, observation, documentation and FGD. The data analysis technique used Miles and Hubeman in the form of data reduction, display and conclusion drawing. The results showed that the professional competence of students in research steps and critical studies in teaching seminars on educational problems in schools was divided into 3, namely before research, during the research process and after the research process. The ability to study critically in deepening the material in the field of study is related to how students construct their knowledge in supporting the professionalism. One indicator of teacher professionalism is self-development through research. Professional competence for a teacher is an importantThe teacher as a scientist has a responsibility to advance science, especially the science that is the specialist. The form of responsibility is to conduct research according to the scientific field.